2014
DOI: 10.1016/j.jaip.2014.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Double-Blind Placebo-Controlled Trial of Dapsone in Antihistamine Refractory Chronic Idiopathic Urticaria

Abstract: Background Management of antihistamine refractory CIU has poorly defined therapeutic options. Objective To evaluate the efficacy of dapsone in antihistamine refractory CIU compared to placebo. Methods Twenty-two patients with antihistamine refractory CIU were randomly assigned to 100 mg of dapsone daily or placebo for 6 weeks in a 14 week double-blind, placebo-controlled crossover trial. Endpoints were measured from a daily diary reflecting weekly hive score (WHS) and weekly itch score (WIS) and a visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 39 publications
4
30
0
4
Order By: Relevance
“…One recent double-blind, placebo study of dapsone suggests efficacy [106] but the placebo group has very low response rate so the efficacy may be inflated. Sulfasalazine is better studied [107] than most of the other agents listed but without clear control groups.…”
Section: Resultsmentioning
confidence: 99%
“…One recent double-blind, placebo study of dapsone suggests efficacy [106] but the placebo group has very low response rate so the efficacy may be inflated. Sulfasalazine is better studied [107] than most of the other agents listed but without clear control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports [52] and, recently, a double-blind placebo-controlled study [53] support the effectiveness of dapsone, an antiinflammatory drug, in patients with recalcitrant CSU.…”
Section: Other Drugsmentioning
confidence: 93%
“…The current international urticaria guideline was unable to provide a recommendation for or against the use of dapsone and its benefits remain unclear. However, results from a double‐blind, placebo‐controlled trial of dapsone have shown promising efficacy for this therapeutic agent in patients with antihistamine refractory chronic urticaria . It is worth noting, however, that this trial used the Visual Analogue Scale rather than the recommended 7‐day Urticaria Activity Score (UAS7) to assess treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%